2022
DOI: 10.3390/polym14173496
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Graphene Oxide on Aging Properties of Polyurethane-SBS Modified Asphalt and Asphalt Mixture

Abstract: In order to clarify the effect of the new nano-material graphene oxide on the performance of Polyurethane-SBS modified asphalt and asphalt mixture under the effect of thermal aging, the cracking process of semicircular bending test (SCB) specimens was monitored in situ based on computer vision image processing technology (OpenCV), and the modified asphalt and the cracking characteristics of the modified asphalt and mixture were further analyzed by the tests of semicircular three-point bending and aggregate con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Meanwhile, the δ master curves exhibit significant fluctuations and plateaus ranging from 10 −3 to 10 0 Hz. This behavior suggests the occurrence of a phase transition in this frequency zone, providing evidence for the formation of a crosslinking grid structure between PUP and asphalt [ 47 , 48 ]. It is worth noting that a higher G * and a lower δ imply less energy loss under repeated loads.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the δ master curves exhibit significant fluctuations and plateaus ranging from 10 −3 to 10 0 Hz. This behavior suggests the occurrence of a phase transition in this frequency zone, providing evidence for the formation of a crosslinking grid structure between PUP and asphalt [ 47 , 48 ]. It is worth noting that a higher G * and a lower δ imply less energy loss under repeated loads.…”
Section: Resultsmentioning
confidence: 99%
“…of a crosslinking grid structure between PUP and asphalt [47,48]. It is worth noting that a higher G * and a lower δ imply less energy loss under repeated loads.…”
Section: Frequency Sweep Test Resultsmentioning
confidence: 99%
“…Additionally, a few studies have reported on the enhancement effect of GO on the performance of SBS-MA. As a reinforcing agent, GO can remarkably improve the aging resistance of asphalt mixtures, owing to its ability to reduce the degradation of SBS modifiers and change the crosslinked composite structure of asphalt [ 23 , 24 ]. Favourable high-temperature rheological properties were also obtained for the asphalt binder by doping SBS with GO to form a composite modifier [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars have studied the modifed asphalt with the hindered amine light stabilizer GW-944 [22]. Te study found that the additive could hardly afect the thermal and fatigue performance of asphalt after UV ageing treatment, but it can achieve the improvement of the low-temperature property of asphalt materials [22,23]. Te study also found that the additive should not be incorporated into the base asphalt, and the test results suggested that the UV ageing resistance modifer should be used into SBS-and SBR-modifed asphalt [22,23].…”
Section: Introductionmentioning
confidence: 99%